Diagnostic validity of line bisection in the acute phase of stroke. (February 2016) - Sperber, Christoph; Karnath, Hans-Otto
Abstract: The line bisection task is commonly depicted as a valid diagnostic tool to help differentiate between primary visual field defects and spatial neglect. However, recent studies have addressed possible drawbacks in the acute phase after stroke onset. We investigated these critical assumptions in a large and homogeneous sample of 180 acute stroke patients. Line bisection, cancellation performance, copying, and primary visual field defects were assessed in 180 acute right-hemispheric stroke patients. Effects of visual field defects and concurrent spatial neglect on line bisection were analyzed by multiple regression to account for possible additive and interactive effects. The relation between line bisection and other tests applied in spatial neglect was explored by factorial analysis. We found no evidence for the existence of a contralesional 'hemianopic line bisection error' in acute patients with primary visual field defects. Such patients even showed a more pronounced ipsilesional line bisection error. Second, the factorial analysis revealed that the line bisection task on the one hand and cancellation/copying tasks on the other were represented by different factors, indicating that they make different cognitive demands. In the acute phase of stroke, line bisection does not appear to be a valid task to diagnose neither primary visual field defects nor spatial neglect (the latter as defined by its core symptoms (cf., Karnath and Rorden, 2012 ) which are typically captured with cancellation/copying tasks). Highlights: Line bisection was examined in 180 acute right hemisphere stroke patients. A contralesional bisection error was not found in patients with visual field defects. Line bisection assessed a different behavior than cancellation/copying. In acute stroke, line bisection is not a valid task to diagnose spatial neglect.